Risk Assessment of Driver Performance in the Oil and Gas Transportation Industry: Analyzing the Relationship Between Driver Vigilance, Attention, Reaction Time, and Safe Driving Practices - Al-Baraa Abdulrahman Al-Mekhlafi; Ahmad Shahrul Nizam Isha; Nicholas Chileshe; Ahmed Farouk Kineber; Muhammad Ajmal; Abdullah O. Baarimah; Al-Hussein M.H. Al-Aidrous (Cell press in collaboration with Elsevier, 2024)
Indexed by WOS/ Scopus